OPTIMALISASI JUMLAH TIPE RUMAH YANG AKAN DIBANGUN DENGAN METODE SIMPLEKS PADA PROYEK PENGEMBANGAN PERUMAHAN - Sudarsana, Dewa Ketut (Jurnal Ilmiah Teknik Sipil; Vol. 13, No. 2 Juli 2009, 2009)
The challenges that have been faced by housing developers are to formulate the quantity of house type to be built, thus they should fulfill the market aspect, government rule and gain the maximum profit from their sales. The objective of this study is to formulate the best composition of house type quantity, which can result in maximum profit. The data was analyzed by using Simplex method. A case study was taken at development of Taman Wira Umadui Housing in Denpasar. The types of the house to be built were categorized into types A, B and C. Type-A (60/120) has 60 m2 of house area, 120 m2 of land area and the price IDR 285.000.000 per unit. Type B (45/100), which has 45 m2 of house area and 100 m2 of land area, was priced at IDR 230.000.000 per unit. And type C (36/80), which has 36 m2 of house area and 80 m2 of land area, cost IDR 190.000.000 per unit. The result of this study showed that the optimum composition of house type quantity is 28 unit of type A, 17 unit of type B and 54 unit of type C. The maximum profit that could be earned from this composition was IDR 7.171.000.000.
Keywords: Optimizing, simplex method, house type quantity.